Pengaruh Formulasi Pasta Gigi Kombinasi Ekstrak Etanol Daun Sirih (Piper betle L), Biji Pinang (Areca catechu) dan Gambir (Uncaria gambir) terhadap Hambatan Pertumbuhan Bakteri Streptococcus Mutans - Nilasary Rochmanita Suparno; Citra Monika Sainti Camalin; Chintami Setyawan Putri (STIKES MUHAMMADIYAH KLATEN, 2020)
Appropriate use of toothpaste is an effort to reduce problems in the oral cavity, namely reducing plaque that causes dental caries. One of the advantages of herbal toothpaste compared to some toothpastes on the market is that it does not use Sodium Lauryl Sulphate (SLS) which often causes side effects on the oral mucosa. Betel leaf, areca nut and gambier are herbal ingredients which are proven to be effective in inhibiting bacterial growth. To determine the combination of betel leaf, areca nut, and gambier extract ethanol toothpaste in inhibiting the growth of Streptococcus mutans bacteria. This type of research was true experimental laboratories with a post-test only control group design. The study was tested using the well diffusion method with the treatment group namely negative control toothpaste (K-), combination of betel leaf, areca nut, and gambier extract ethanol toothpaste with concentrations of 10%; 1.5%; 0.5% (F1) and 20%; 3%; 1% (F2), positive control toothpaste (K+). The measurement of inhibition zone is carried out with a caliper. Data were analyzed using One Way Anova and Post Hoc LSD tests. The statistical analysis showed significant differences between groups (p<0.05), except between the (K-) and (K+) groups, as well as between the F1 and F2 groups (p>0.05). Combination of betel leaf, areca nut, and gambier extract ethanol toothpaste has an effect on the inhibition of the growth of Streptococcus mutans bacteria.